2019
DOI: 10.1130/b31840.1
|View full text |Cite
|
Sign up to set email alerts
|

Erosion rates and sediment flux within the Potomac River basin quantified over millennial timescales using beryllium isotopes

Abstract: Beryllium isotopes measured in detrital river sediment are often used to estimate rates of landscape change at a basin scale, but results from different beryllium isotope systems have rarely been compared. Here, we report measurements of in situ and meteoric 10 Be (10 Bei and 10 Bem, respectively) along with measurements of reactive and mineral phases of 9 Be (9 Bereac and 9 Bemin, respectively) to infer long-term rates of landscape change in the Potomac River basin, North America. Using these data, we compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 99 publications
3
41
0
Order By: Relevance
“…2.1.1. | Pre-colonial period before European arrival Geologic (pre-European) rates of erosion varied across the Chesapeake watershed with greater erosion in basins that are steeper and have more precipitation (Portenga et al, 2019). Notably, the Piedmont physiographic province, located between the mountains and Coastal Plain, had low natural sediment yields compared to current high yields (Gellis et al, 2009).…”
Section: The Role Of Land Use Historymentioning
confidence: 99%
“…2.1.1. | Pre-colonial period before European arrival Geologic (pre-European) rates of erosion varied across the Chesapeake watershed with greater erosion in basins that are steeper and have more precipitation (Portenga et al, 2019). Notably, the Piedmont physiographic province, located between the mountains and Coastal Plain, had low natural sediment yields compared to current high yields (Gellis et al, 2009).…”
Section: The Role Of Land Use Historymentioning
confidence: 99%
“…Bioturbation homogenizes 10 Bei concentrations in soils (Brown et al, 1995;Granger et al, 1996;Schaller et al, 2018), and 10 Bei erosion rates are therefore considered to be insensitive to widespread shallow erosion. This insensitivity allows 10 Bei erosion rates to be a useful gauge of pre-disturbance rates of landscape change (Ferrier et al, 2005;Portenga et al, 2019;Schmidt et al, 2018;Vanacker et al, 2007); exceptions have been noted where human land use is intensive (i.e. Schmidt et al, 2016) or the effects of human land use are exacerbated by climate extremes (i.e.…”
Section: In Situ 10 Be and Meteoric 10 Be Erosion And Denudation Metricsmentioning
confidence: 99%
“…Recently derived equations allow erosion rates and denudation rates to be calculated from measurements of 10 Bem and the chemically-similar, non-cosmogenic 9 Be, which is weathered out of mineral grains ( 9 Bereac; Willenbring and von Blanckenburg, 2010;von Blanckenburg et al, 2012). 10 Bem erosion and 10 Bem/ 9 Bereac denudation rates have been used to quantify landscape evolution over a variety of spatial scales for long-established river basins (Dannhaus et al, 2018;Deng et al, 2020;Harrison et al, 2021;Portenga et al, 2019;Rahaman et al, 2017;Wittmann et al, 2012Wittmann et al, , 2015 and has shown particular promise in quantifying landscape dynamics in quartz-poor landscapes (Deng et al, 2020;Rahaman et al, 2017).…”
Section: In Situ 10 Be and Meteoric 10 Be Erosion And Denudation Metricsmentioning
confidence: 99%
“…10 Bemet is then delivered to Earth's surface via precipitation or as dry deposition at a flux of 0.1 -2 x 10 6 atoms cm -2 yr -1 followed by dissolved export in runoff, or depending on retentivity, adsorption onto fine-grained, reactive surfaces, typically clays and Fe-oxyhydroxides, in soil horizons at the Earth's surface (Willenbring and von Blanckenburg, 2010). 10 Bemet has been used as a tracer of Earth surface processes, including estimating erosion rates at the soil profile and river catchment scales, soil residence times, ages of landforms over millennial to million-year timescales, and paleo-denudation rates from marine sedimentary records (Pavich et al, 1986;McKean et al, 1993;Jungers et al, 2009;Willenbring and von Blanckenburg, 2010;von Blanckenburg and Bouchez, 2014;Wittman et al, 2015;von Blanckenburg et al, 2015;Portenga et al, 2019;Jelinski et al, 2019). Prerequisites to interpreting the concentrations and isotope ratios (i.e.…”
Section: Introductionmentioning
confidence: 99%